Ventilator-Associated Pneumonia in Dr. Soetomo General Hospital Surabaya - Ismi Masyithah; Usman Hadi; Eko Budi Koendhori (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2021)
Introduction: Ventilator-associated pneumonia (VAP) is one of the most common nosocomial infections in the intensive care unit (ICU). Mechanically, ventilated patients have a higher risk of VAP. VAP can increase morbidity, mortality, and treatment costs. However, Indonesia lacks data about VAP. The objective of this study was to find out the characteristics of VAP in Dr. Soetomo General Hospital, Surabaya, in the period of August 2017 until August 2018.Methods: This was a cross-sectional study by assessing medical records of the patients in ICU. The variables observed in this study were age, gender, outcome, length of stay in the ICU (LOSICU), and primary diagnosis. The inclusion criteria were the patients who have been using mechanical ventilation at least 2 x 24 hours in the ICU and confirmed VAP. The data were analyzed descriptively by using Microsoft Excel 2016.Results: A total of 18 VAP patients were diagnosed. VAP patients were dominated male (55.6%). The mean of LOSICU was 22.83 ± 11.24 days, and the mortality rate of VAP patients was high (55.6%). 30% of VAP patients had Guillain-Barre Syndrome (GBS) as the primary diagnosis, and 16.65% had Congenital Heart Disease (CHD).Conclusion: Most VAP patients were male and had prolonged stays. The mortality rate of VAP patients was still high. GBS was the most frequent of primary diagnoses in patients with VAP and also CHD.